Stakeholders’ Perceptions of Performance-Based Capitation Design Using Chronic Disease Indicators at Primary Health Care Facilities - Sitorus, Susy Hartati Novintry (BPJS Kesehatan, 2025)
Based on BPJS Kesehatan’s utilization review data (Social Security Administrative body for Health) until December 2023, only 32% of 273 primary healthcare facilities met the fourth level for the Controlled prolanis participant ratio (RPPT) indicator. This indicator reflects the percentage of Prolanis-registered patients diagnosed with Diabetes Mellitus (DM) or Hypertension (HT) who have achieved controlled fasting blood glucose (for DM) or controlled blood pressure (for HT), with a performance target of ≥ 5%. Meanwhile, 42% of facilities reached the Angka Kontak (AK/Contact Number) target, which measures the number of participants who contacted Primary Health Care Facilities (FKTP) compared to the total registered participants, multiplied by 1,000; the target is ≥ 150 per mille. However, 83% of facilities achieved the Non-Specialist Referral Ratio (RRNS) target, which compares the number of non-specialist case referrals to total referrals; the target is ≤ 2%. These findings highlight the need for stronger motivation mechanisms, such as financial incentives, to support FKTP in achieving better scores in the Performance-Based Capitation (KBK) model. This study explores stakeholder perceptions regarding an incentive-based KBK model using the RPPT indicator in FKTPs in Medan. Stakeholders shared several key perspectives: (1) RPPT targets should range between 5% and 10%, with incentives tied to rating levels; (2) intermediate outcome indicators should include HbA1c for DM and blood pressure for HT; (3) incentive payments should be allocated to FKTPs and managed to strengthen chronic disease services; and (4) these payments must be consistent and sustainable.